The process of the process of internationalisation: cognitive and behavioural perspectives in small ventures - Vlačić, Božidar (2022)
This paper investigates the internationalisation decision-making process from the perspective of the decision maker’s cognition. The aim is to advance the theoretical arguments that help explain the heterogeneous patterns of internationalisation for smaller ventures. Our framework includes the four-stage psychological process of decision-making: perception, options, evaluation and choice under the interactive effect of two-cognitive systems, namely experiential (Sys-1) and analytical (Sys-2). Based on interviews with six owners operating small ventures in high-tech industries, we found that accelerated patterns of internationalisation can be associated with increased levels of decision-makers experiential reasoning combined with lower levels of analytical reasoning interventions through the entire decision-making process of internationalising. Conversely, incremental and slower patterns of internationalisation can be associated with increased levels of analytical reasoning and lower levels of experiential interventions. Overall, we supplement the extant approaches to internationalisation with the Dual Process Theory of how individuals process information to make decisions.